The Practicality of Teaching Materials on Types of Crab in the Mangrove Forest Area to Improve Critical Thinking Skills for Islamic High School Students - Nahri Fauzan; Mochamad Arief Soendjoto; Muhammad Zaini (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2021)
The crabs are organisms that have a major role in the mangrove ecosystem. The preservation of the mangrove ecosystem cannot be separated from the roles and responsibilities of humans. This can be started by creating awareness and practicing thinking skills to provide solutions to various existing environmental problems. According to the results of the TIMSS study, the low scientific ability of Indonesian students, especially its implementation in the form of scientific literacy, has not shown a good improvement so that learning innovations are needed, one of which is the manufacture of environment-based teaching materials. The purpose of this study was to describe the practicality of the teaching materials "Crab Types in the Mangroves Area" in training students' critical thinking skills at MAN Tanah Laut. The type of research used is the Tessmer formative test. The research data were analyzed descriptively, practical data included the feasibility of using teaching material and student responses, indicating that the teaching materials developed were practical for use in learning and could improve the critical thinking skills of MA students.Abstrak Kepiting merupakan organisme yang memiliki peran besar dalam ekosistem mangrof. Kelestarian ekosistem mangrof tidak luput dari peran dan tanggung jawab manusia. Hal ini dapat dimulai dari menciptakan kesadaran dan melatih keterampilan berpikir agar dapat memberikan solusi-solusi dari berbagai permasalahan lingkungan yang ada.  Hasil studi TIMSS menunjukkan rendahnya kemampuan sains siswa Indonesia terutama implementasinya dalam bentuk literasi sains belum menunjukkan adanya peningkatan yang baik sehingga diperlukan inovasi pembelajaran salah satunya dengan pembuatan bahan ajar berbasis lingkungan. Tujuan penelitian ini adalah untuk mendeskripsikan kepraktisan Bahan Ajar “Jenis Kepiting di Kawasan Mangrof” dalam melatihkan keterampilan berpikir kritis siswa MAN Tanah Laut. Jenis penelitian yang digunakan adalah uji formatif Tessmer. Data hasil penelitian dianalisis secara deskriptif, data kepraktisan meliputi kepraktisan penggunaan bahan ajar dan respon siswa, menunjukkan bahwa bahan ajar yang dikembangkan praktis untuk digunakan dalam pembelajaran dan dapat meningkatkan kemampuan berpikir kritis siswa MA.